BRAND SUSTAINABILITY STRATEGY DEVELOPMENT: THE ROLE OF SOCIAL MEDIA MARKETING AND MARKETING MANAGEMENT - Zaenal Aripin; Wawan Ichwanudin; Ijang Faisal (Yayasan Kreatif Indonesia Emas, 2023)
In the context of modern business that is increasingly intertwined with sustainability issues, the development of a brand sustainability strategy is becoming essential for companies that want to not only survive but also thrive. Social media marketing and marketing management are emerging as key forces in shaping sustainable brand identities, guiding organizations towards responsible business practices and empowering consumers. This research aims to explore the role of social media marketing and marketing management in the development of brand sustainability strategies. A key focus is on identifying how social media engagement and marketing management strategies can shape consumer perceptions of brands and lead to the implementation of sustainable business practices. This research uses a descriptive qualitative approach with data collection through in-depth interviews with marketing, brand management, and social media experts in organizations that have successfully integrated brand sustainability. Document analysis was also conducted to investigate the organization's social media campaigns, marketing materials, and sustainability reports. The results show that social media marketing plays an important role in conveying brand sustainability messages, creating consumer engagement, and building awareness of responsible business practices. Meanwhile, marketing management serves as a catalyst for integrating sustainability values in all aspects of an organization's marketing strategy and operations. Employee engagement and interdepartmental collaboration are key to the successful implementation of a brand's sustainability strategy.